“Spinster”: a Portrait of an Unmarried Woman in the Late Soviet Era in the Lithuanian Press - Vaitkutė, Goda (Vilnius University Open Series, 2024)
The work examines a portrait of an unmarried woman called “spinster” of the late Soviet era (1968–1985), in the Soviet Lithuanian press. This research is not about unmarried or childless woman, but only those who have been considered “spinster”. The existence of a “spinster” in the press is not analyzed at all. It should be noted, that the very concept of the “spinster” is a problem, which is why this work examines its definition based on the understanding of the time.
Keywords: spinster; old maid; late Soviet era; portrait; image; press; woman in the Soviet era; unmarried woman; childless woman; moteris sovietmečiu